ASSESSMENT OF IMMUNE STABILITY IN BREAST CANCER SUBJECTS - A.O, Oluboyo; S.C, Meludu; C.C, Onyenekwe; B.O, Oluboyo; G.U, Chianakwanam; C, Emegakor (European Scientific Journal, ESJ, 2014)
Cancer is a cause of death worldwide and the socio-economic impact of cancer is enormous and disturbing. Breast cancer is becoming a significant health concern for women across Nigeria and immune instability may be responsible. Therefore, the present study was designed to assess the immune stability of breast cancer subjects using CD4 + T cell, CD8 + T cell counts and the CD4/CD8 ratio. One hundred subjects were randomly recruited for the study and grouped into Breast cancer subjects (BCA) (n=50) and control (n=50). CD4 + T cells (Î¼l/count) and CD8 + T cells (Î¼l/count) were estimated using flow cytometric method while CD4/CD8 ratio was calculated from the values obtained from the CD4 + T cells and CD8 + T cells. CD4+ T cells and CD8+ T cells showed significant decrease (p<0.05) in the breast cancer subjects compared to the control subjects. TheÂ suppressed CD4 + and CD8 + T cell counts in breast cancer subjects mayindicate immune instability in the cancer subjects.